Comparaciones entre medición directa y estimación del metano producido por estiércol bobino: Caso Julián y Severino, cantón Bolívar, provincia de Manabí - Delgado Chávez, Milena Soledad (2015)
This research was carried out in a micro-watershed of the Carrizal river in Julian and Severino. The main objective was to measure the level of methane emissions from livestock manure using biodigesters. The inductive method used in this research included two variables: independent —livestock manure —and dependent— methane emissions. —In order to achieve the specific objective —to measure the level of methane emissions from livestock manure using “sausage” tube biodigesters —10 biodigesters were built. For each biodigester, 2.5 kg of livestock manure were used, and the results were obtained after a reaction period of 45 days. Methane gas production was measured at a Leachate and Gas Laboratory, delivering accurate gas emission detection from each sample where it determined an 47.51% methane emission by dairy cattle and 49.97% of the gas emissions from the non-dairy cattle. With the IPCC software, methane emission was estimated with equations that consider number of livestock in the area and all the related variables, where the results were 33.33% emission dairy cattle and 66.67% methane emission for the contribution of non-dairy cattle.